Achieving fruit, juice, and vegetable recipe preparation goals influences consumption by 4th grade students - Baranowski Tom; Zakeri Issa; Watson Kathy B; Cullen Karen W; Baranowski Janice H (BMC, 2007)
Abstract Background Including children in food preparation activities has long been recommended as a method to encourage children's consumption, but has not been evaluated. Goal setting is also a common component of behavior change programs. This study assessed the impact of attaining goals to prepare fruit-juice or vegetable recipes on student fruit and vegetable consumption as part of a 10-week fruit and vegetable intervention for fourth grade students. Methods At six of the 10 sessions, students (n = 671) selected a fruit-juice or vegetable recipe to prepare at home before the next session. Students returned parent-signed notes reporting their child's goal attainment. Baseline and post consumption were assessed with up to four days of dietary recalls. Analyses included regression models predicting post consumption from the number of fruit-juice or vegetable recipe preparation goals attained, controlling for baseline consumption. Results In general, girls and Hispanic students achieved the most recipe preparation goals. For students with highest baseline fruit-juice consumption, post fruit-juice consumption was higher by about 1.0 serving for those achieving 2 or 3 fruit-juice recipe preparation goals. Post vegetable consumption was highest for students reporting the highest baseline vegetable consumption and who achieved two or three vegetable recipe preparation goals. In general, recipe goal setting was a useful procedure primarily for those with high baseline consumption. Conclusion This is one of the first reports demonstrating that home recipe preparation was correlated with dietary change among children.